PRZYGODY PRAWDY John D. Caputo. Truth. Philosophy in Transit. London: Penguin Books, 2013. 304 P. - Szaj, Patryk (Porównania, 2015)
PRZYGODY PRAWDY John D. Caputo. Truth. Philosophy in Transit. London: Penguin Books, 2013. 304 P.